2007
DOI: 10.1111/j.1525-1594.2007.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hemodialysis on P‐Wave Signal‐Averaged Electrocardiogram Findings

Abstract: The role of P-wave signal-averaged electrocardiography (P-SAECG) in the prediction of atrial fibrillation (AF) attacks has been validated in various disease states. In the present study, we aimed to investigate the effect of hemodialysis (HD) on P-SAECG parameters and to determine the related risk factors that might affect those parameters. Ninety-one HD patients and 68 controls were included. Hemoglobin levels, serum electrolytes, arterial pH, and interdialytic weight changes were assessed. P-wave duration (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…P wave duration significantly increased from a beginning mean of 27 (9) ms to an ending mean of 52 (11) ms (P < .001). Ozcan et al [21] showed that predialysis and postdialysis mean P wave dispersions significantly increased in patients undergoing dialysis when compared with control participants, but the mean voltage of predialysis and postdialysis LP20 were significantly reduced (P < .05).…”
Section: Discussionmentioning
confidence: 96%
“…P wave duration significantly increased from a beginning mean of 27 (9) ms to an ending mean of 52 (11) ms (P < .001). Ozcan et al [21] showed that predialysis and postdialysis mean P wave dispersions significantly increased in patients undergoing dialysis when compared with control participants, but the mean voltage of predialysis and postdialysis LP20 were significantly reduced (P < .05).…”
Section: Discussionmentioning
confidence: 96%
“…6 Studies of P-wave characteristics on electrocardiograms during hemodialysis point to increased intra-atrial conduction abnormalities developing during the hemodialysis procedure, which correlate with changes in potassium and calcium concentrations during the treatment. 19,20 The Heart and Soul study prospectively studied the relationship between AF and renal function. 21 These patients tended to have preserved renal function; the cutoff point between the middle and lowest tertiles was an estimated glomerular filtration rate (eGFR) of 62 mL/min/1.73 m 2 .…”
Section: The Epidemiology Of Af In Patients With Esrd Compared With Tmentioning
confidence: 99%
“…These variations, especially dispersion of the QT interval caused by so-called ''late potentials,'' initially were purported to predict reentrant arrhythmias in patients with ischemic heart disease or cardiomyopathy (15). A number of studies (16)(17)(18)(19)(20)(21)(22) have applied this method to patients undergoing hemodialysis to understand the dialysis-associated risk for cardiac arrhythmias. With one exception (18), all studies showed an increase in late potentials in patients during hemodialysis (16,17,(19)(20)(21)(22).…”
Section: Indirect Evidence: Surrogate Outcomesmentioning
confidence: 99%